Studi Komparatif Asuransi Shari’ah dan Konvensional - Moh. Asra; Rizqiyah Rizqiyah (Program Pascasarjana Universitas Ibrahimy, 2019)
Insurance is an institution engaged in services and helping people. In Arabic, insurance is called